The Effect of Virtual Education in Parenting Skills on the Parenting Sense of Competence in First-time Mothers with a 0-2-year-old Baby: A Quasi-experimental Study - Fatemeh Nouri; Neda Jamalimoghadam; Mitra Edraki; Elham Mirshah (Shiraz University of Medical Sciences, 2023)
Background: Parental competence is a key aspect of parenting. Since they have no previous experienceof having a baby, first-time mothers should acquire certain skills to be competent enough in caring fortheir baby. The present study aimed to investigate the effect of virtual education in parenting skills onthe parenting competence of first-time mothers with a 0-2-year-old baby.Methods: This quasi-experimental study was conducted through convenience sampling; 72 first-timemothers were selected from 12 healthcare centers, 62 of whom met the criteria for entering the study,and divided into an experimental (n=31) and a control (n=31) group. The mothers in the experimentalgroup received virtual education in parenting skills in six sessions, each lasting 10 minutes for twoweeks. The data were collected using a demographics questionnaire and Gibaud-Wallston's parentingsense of competence scale. Sense of competence was assessed in three stages: before, immediatelyafter, and one month after the completion of the intervention. The collected data were analyzed usingSPSS v. 22 at a significance level of less than 0.05.Results: Results showed a statistically significant increase in the experimental group's parentingcompetence mean score immediately and one month after the intervention (P<0.001). There was astatistically significant difference between the mean scores of the study groups as measured immediatelyafter (P=0.043) and one month after the intervention (P<0.001).Conclusion: Virtual education of parenting skills could have a positive impact on the mothers'parenting competence. It is suggested that first-time mothers should be educated in parenting skills ona face-to-face basis in maternity wards and online after discharge.